Biological Properties, Bioactive Constituents, and Pharmacokinetics of Some Capsicum spp. and Capsaicinoids - Batiha, Gaber El-Saber; Alqahtani, Ali; Ojo, Oluwafemi Adeleke; Shaheen, Hazem M.; Wasef, Lamiaa; Elzeiny, Mahmoud; Ismail, Mahmoud; Shalaby, Mahmoud; Murata, Toshihiro; Zaragoza-Bastida, Adrian; Rivero-Perez, Nallely; Magdy Beshbishy, Amany; et al. (International Journal of Molecular Sciences, 2020)
Pepper originated from the Capsicum genus, which is recognized as one of the most predominant and globally distributed genera of the Solanaceae family. It is a diverse genus, consisting of more than 31 different species including five domesticated species, Capsicum baccatum, C. annuum, C. pubescen, C. frutescens, and C. chinense. Pepper is the most widely used spice in the world and is highly valued due to its pungency and unique flavor. Pepper is a good source of provitamin A; vitamins E and C; carotenoids; and phenolic compounds such as capsaicinoids, luteolin, and quercetin. All of these compounds are associated with their antioxidant as well as other biological activities. Interestingly, Capsicum fruits have been used as food additives in the treatment of toothache, parasitic infections, coughs, wound healing, sore throat, and rheumatism. Moreover, it possesses antimicrobial, antiseptic, anticancer, counterirritant, appetite stimulator, antioxidant, and immunomodulator activities. Capsaicin and Capsicum creams are accessible in numerous ways and have been utilized in HIV-linked neuropathy and intractable pain.